Impact of External Sources of Indole Acetic Acid and 2,3,5-Triiodobenzoic Acid on Alkaloid Production and Their Relationships with Primary Metabolism and Antioxidant Activity in Annona emarginata (Schltdl.) H. Rainer - Martin, Bruna Cavinatti [UNESP]; De-la-Cruz-Chacón, Ivan; Mimi, Carolina Ovile [UNESP]; Boaro, Carmen Silvia Fernandes [UNESP]; Campos, Felipe Girotto [UNESP]; Moreira-Coneglian, Inara Regiane [UNESP]; Ferreira, Gisela [UNESP] (MDPI, 2024)
Annona emarginata is a native Brazilian species capable of producing at least ten alkaloids of ecological, agronomic, and pharmacological importance. Some studies have explored the effect of external phytoregulators on the production of alkaloids, including the effect of auxins, which, like alkaloids, derive from the shikimic acid pathway. Thus, this study aimed to evaluate how indole acetic acid (IAA) and its inhibitor 2,3,5-triiodobenzoic acid (TIBA) impact the production of alkaloids and the primary metabolism of A. emarginata, which brings advances in the understanding of the mechanisms of alkaloid synthesis and can aid in the bioprospection of molecules of interest in Annonaceae. The design was completely randomized, with three treatments (control, IAA [10−6 M] and TIBA [10−6 M]) and five collection times (12, 36, 84, 156, and 324 h). The following variables were analyzed: total alkaloids, alkaloid profile, nitrate reductase activity, gas exchange in photosynthesis, chlorophyll a fluorescence, sugars, starch, and antioxidant activity. Of the twelve alkaloids analyzed, discretine and xylopine were not detected in the control plants; however, both were detected when IAA was applied (in roots and leaves) and xylopine (in roots) when the inhibitor was applied. The alkaloid asimilobine was not detected with the use of TIBA. Variations in alkaloid concentrations occurred in a punctual manner, without significant variations in photosynthesis and nitrate reductase activity, but with variations in the antioxidant system and sugar concentrations, mainly at 156 h, when the highest alkaloid concentrations were observed with the use of TIBA. It could be concluded that IAA is capable of selectively modulating the production of alkaloids in A. emarginata, either due to an external source or by the application of its inhibitor (TIBA).
Keywords: Annonaceae; IAA; nitrogenous secondary metabolites; plant regulators; TIBA